2013
DOI: 10.1038/eye.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, treatment, and outcomes in presumed intraocular tuberculosis: experience from Newcastle upon Tyne, UK

Abstract: Purpose To report the clinical manifestations and treatment outcomes of patients with presumed intraocular tuberculosis (TB) seen at the Newcastle Uveitis Service, Royal Victoria Infirmary, Newcastle upon Tyne, UK over a 10-year period. Methods Retrospective review of case notes. Results A total of 21 patients were identified. Occlusive retinal vasculitis was the commonest ophthalmological presentation (12 patients). Eight patients (38%) were found to have underlying active systemic TB (four with mediastinal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 22 publications
4
25
1
1
Order By: Relevance
“…A total of 5 studies reported relevant history of previous TB (range 4.8%–11.1%) 45, 50, 62, 73, 76 , 7 studies on contact history of TB (range 12.1%–70.6%) 26,46,51,59,63,64,74 and 12 studies on presence of systemic TB (highest reported rate being 89.4% by Vos and colleagues 74 ). TST, QuantiFERON-TB Gold, and chest X ray were the more common adopted modalities of investigations with 10, 7, and 15 studies (of 28) using the aforementioned tests, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5 studies reported relevant history of previous TB (range 4.8%–11.1%) 45, 50, 62, 73, 76 , 7 studies on contact history of TB (range 12.1%–70.6%) 26,46,51,59,63,64,74 and 12 studies on presence of systemic TB (highest reported rate being 89.4% by Vos and colleagues 74 ). TST, QuantiFERON-TB Gold, and chest X ray were the more common adopted modalities of investigations with 10, 7, and 15 studies (of 28) using the aforementioned tests, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We read with great interest the paper by Manousaridis et al, 1 which adds to the publication by Sanghvi et al, 2 with respect to presumed tuberculous (TB) uveitis in the United Kingdom, and we would commend both sets of authors for these well-presented case series. In the latter 2 it was recommended that a full 6-month course of Anti-TB therapy (ATT) be commenced in all patients with uveitis and latent TB, in whom other causes of uveitis have been ruled out.…”
Section: Sir Liver Failure Following Antituberculosis (Att) Chemothementioning
confidence: 88%
“…Признавая, что отсутствие призна-ков и симптомов туберкулёза лёгких не исклю-чает диагноза туберкулёза глаз, данные авторы вполне обоснованно полагают, что врачам нужны диагностические признаки туберкулёза глаз, не-зависимые от внеглазных туберкулёзных пораже-ний [28]. Некоторые зарубежные авторы, однако, ставят диагноз предполагаемого туберкулёзного хориоретинита на основании положительного кожного туберкулинового теста и в соответствии с ним назначают лечение, в том числе и длитель-ное применение туберкулостатиков [26,29,31]. Обоснованность такого подхода к диагностике и лечению весьма сомнительна.…”
Section: методика исследованияunclassified